Criticism As A Resistance Strategy in Fārūq Juwaidah’s Poems - Zulfa Purnamawati (CMES (Center of Middle Eastern Studies), 2021)
This study aims to reveal the resistance strategy used by Faruq Juwaidah, an Egyptian poet who has high concern for the fate of the Palestinians who are under Israeli Zionist rule. The object of this research material is Risalatun Ila Sarun I and II in which there are resistance values. The method used is a semiotic reading which consists of heuristic and hermeneutic reading. The results of this study indicate that the resistance strategy in Faruq Juwaidah's poetry is criticism. This form of criticism is expressed in characterization which in psychological terms is called labeling. In this term used  tasybīh and isti'ārah, which are the likeness of a pig, dog and cobra. In addition, criticism is also carried out by directly pinning negative traits, such as qabīh "bad", al-mal'un "the cursed", jabbanun "coward" al-fāsiqu "people who do bad things", and al- ' irbidu "a bad person in character". In addition, criticism is also expressed by the satire. The use of satire is a considered effective way to make political and social criticism, especially at the actions taken by Israeli Zionists who have tormented the Palestinian people.Keywords: criticism, characterization, satire, zionist israel, palestine